Risk disclosure and firm performance of Malaysia listed companies - Chan,, Hui Lun, (Universiti Malaysia Sarawak, (UNIMAS), 2015)
This empirical study is conducted to examine whether the level of risk discloses practice in Malaysia and its determinants had contributed to financial firm performance from year 2010-2014. A total of 565 firms selected from Bursa Malaysia listed companies. The indicators of firm performance, such as Tobin's Q and Return on Assets (ROA) acts as depedent variables. Whereas the corporate risk disclosure index (CRD), growth, leverage and firm size as independent variables. The results show leverage and corporate risk disclose (CRD) are positive and significant associated with firm performance (Tobin's Q) from the financial perspective. Howeve, there is no evidene of a significant relationship between growth and firm size with the firm performance. On the other hand, the determinants of leverage and the firm size presence a positive and significant relationship with firm performance (ROA) from accounting perspective. The corporate risk discloses (CRD) and growth show insignificant association with firm performance from an accounting perspective.